The Impact of Translation Method and Shift on Translation Quality at Bilingual Textbooks of Physics, Mathematics and History - Sipayung, Kammer Tuahman (Bina Nusantara University, 2020)
The objectives of this research were; first was to figure out translation methods and shifts that translators applied in translating bilingual textbooks of History, Mathematics, and Physics, which is used in grade seven in Medan, those bilingual textbooks were published by Quadra, Yramawidia, and Yudhishthira. The second was to figure out the impact of translation methods and shifts which dominant on translation quality. The third was to recommend better bilingual textbooks to use based on the translation quality point of view. The researchers used a descriptive qualitative research method with a questionnaire, depth-interview, and observation on a pair of translation to collect the data. The data were analyzed with interactively and non-interactively. Based on the data analysis, the researcher finds that (1) the dominant shift on History textbook is unit shift while the dominant method is a free translation, the dominant shift on Physics is a unit shift and dominant method is a communicative translation, the dominant shift on Mathematics is structure shift and dominant method is communicative translation. The second finding is that the impact of the dominant translation shift and method on the History textbook is negative. At the same time, in Mathematics and Physics are positive. Furthermore, third is in this research; the researcher recommends bilingual textbooks of Mathematics and Physics to use based on translation quality point of view. The well bilingual textbooks can improve students’ language skills, while low translation quality influences bad development to students on learning the language.